Validity, reliability, and item characteristics of cell material science literacy assessment instruments - Wilsa, Asrizal Wahdan; Rusilowati, Ani; Susilaningsih, Endang; Jaja, Jaja; Nurpadillah, Veni (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This study aims to examine the validity, reliability, and item characteristics of scientific literacy assessment instruments on cell material. The scientific literacy ability category includes identifying valid scientific arguments, evaluating the validity of a source, evaluating the use and misuse of scientific information, understanding research design elements and how they impact scientific findings, and reading and interpreting graphical representations of data. The research subjects were students of the 5th semester elementary school teacher education study program. The validity test included content validity using Aiken V validity index and construct validity using Exploratory Factor Analysis (EFA). Reliability test is carried out by looking for the price of the reliability coefficient r with correlation product moment test. The characteristic test is carried out by determining the level of difficulty and discriminating power. The results show that the scientific literacy assessment instrument on cell material is a valid instrument based on the analysis of content validity, construct validity, and item characteristics. Thus, the assessment instrument is suitable for use as an assessment instrument in research to measure students' scientific literacy in cell material.